YouTube Extension of Music Memory - Trena Jordanoska (Kultura (Skopje), 2014)
Individual work approach to collective cultural memory is marked by unprecedented digital tool – Internet. Social networks accelerated the exchange of music artifacts to extremely large numbers of participants. One of the important aspects of the new digital transition is that the improved transfer rates resulted in an audio quality approaching the limits of human hearing. YouTube counter is undoubtedly the best indicator for the presence of these artifacts in virtual reality. The records of the downloads of the “Gangnam Style” song in billion, support the argument for the influence of the new technological means on collective memory. In our research we collected and analyzed the data regarding music posting on YouTube.